Flow pattern and behavior of 40 kWth pulverized torrefied biomass flames under atmospheric and oxy-fuel conditions. (March 2021) - Zabrodiec, D.; Massmeyer, A.; Hees, J.; Hatzfeld, O.; Kneer, R.
Abstract: The combustion of torrefied biomass under oxy-fuel conditions is a promising technological alternative, which has the potential to transform electric and heat generation systems into more sustainable and carbon-neutral forms. This combustion approach combines two complex processes, oxy-fuel and biomass combustion, which still require significant understanding. For this, an experimental study has been conducted considering a series of 40 kWth aerodynamically stabilized pulverized torrefied biomass and coal flames. Given the increasing interest and advantages of substituting coal by biomass in different thermal industrial processes, a set of four experimental conditions was studied and compared. Two torrefied biomass flames, under conventional and oxy-fuel combustion atmospheres, are compared to two similar coal (lignite) operating conditions. The combustion behavior of the flames is assessed by conducting detailed measurements of flow fields, gas compositions, and radiative heat fluxes. Experiments are performed employing a combustion chamber with a simplified configuration. Combined results from the different measurements show that the overall combustion characteristics of torrefied biomass under the two atmospheres are fairly similar. Also, they do not significantly differ from the combustion characteristics observed for the coal flames. Comparatively, the radiative heat fluxes produced by the torrefied biomass flames were higher than those produced by coal. In addition, oxy-fuel flames produced 15–20% lower radiative heat fluxes than the air counterparts. Gas concentration measurements near the flames showed diverse results attributed to small differences in the turbulent flow fields and fuel composition. The presented analysis of results can also contribute to the retrofitting of conventional pulverized coal firing systems for operation under oxy-fuel conditions with torrefied biomass. Highlights: An experimental comparison of torrefied biomass and lignite flames was made. Detailed flow field, gas composition, and radiative flux measurements are presented. Radiative heat flux profiles between coal and torrefied biomass flames are similar. Torrefied biomass produced higher radiative heat fluxes than lignite. Smaller inner recirculation zone and lower turbulence observed in oxy-fuel cases.